2021
DOI: 10.1007/978-3-030-79725-6_49
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Digital Utilization in Accounting to Enhance MSMEs’ Performance During COVID-19 Pandemic: Case Study in Semarang, Central Java, Indonesia

Abstract: Since the COVID-19 pandemic is grappling the world, digital adoption in many aspects is strongly needed by the MSMEs. During pandemic COVID-19, the need for digitalization emphasized MSMEs' adopt digital technology in accounting. Digital utilization can boost MSMEs accounting skills, both financial accounting and management accounting skills. Digital utilization in financial and management accounting help MSMEs calculate, report, transmit, and interpret financial data faster, more efficient, and effective. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
14

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 8 publications
0
23
0
14
Order By: Relevance
“…A study revealed that innovation capabilities and technology had a signi cant and favorable impact on the pandemic-related business resiliency in the handicraft sector as part of the small-scale industry [78]. According to another study, using digital technology to give more precise, e cient, and effective, nancial reports and nancial data could help develop accounting abilities, both management and nancial, which have a major favorable impact on MSMEs' performance throughout the pandemic [79]. Through frameworks that foster the development of digital and entrepreneurial skills through education and training programs, policies should address the obstacles to digital entrepreneurship (Reyes 2021).…”
Section: Policy Implications Of the Researchmentioning
confidence: 99%
“…A study revealed that innovation capabilities and technology had a signi cant and favorable impact on the pandemic-related business resiliency in the handicraft sector as part of the small-scale industry [78]. According to another study, using digital technology to give more precise, e cient, and effective, nancial reports and nancial data could help develop accounting abilities, both management and nancial, which have a major favorable impact on MSMEs' performance throughout the pandemic [79]. Through frameworks that foster the development of digital and entrepreneurial skills through education and training programs, policies should address the obstacles to digital entrepreneurship (Reyes 2021).…”
Section: Policy Implications Of the Researchmentioning
confidence: 99%
“…Digitalisasi akuntansi juga dapat meningkatkan kinerja keuangan dan non-keuangan usaha mikro, kecil, dan menengah (UMKM) (Bygren, 2016;Möller et al, 2020). Sebuah penelitian yang dilakukan di Semarang, Indonesia, bertujuan untuk menganalisis bagaimana kinerja UMKM dipengaruhi oleh digitalisasi akuntansi (Apriyanti & Yuvitasari, 2021). Studi tersebut menemukan bahwa peran teknologi informasi menempati posisi penting dalam mendukung profit dan produktivitas.…”
Section: Pendahuluanunclassified
“…Digitalisasi akuntansi dapat memberikan dampak positif terhadap kinerja usaha mikro, kecil, dan menengah (UMKM) (Seseli et al, 2023). Pemanfaatan teknologi digital dalam akuntansi dapat meningkatkan kemampuan akuntansi keuangan dan manajemen, membuat data dan laporan keuangan menjadi lebih akurat, efektif, dan efisien (Apriyanti & Yuvitasari, 2021). Hal ini dapat meningkatkan kinerja keuangan dan non-keuangan UMKM (Gherman et al, 2021).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations